Influence of Microstructure on the Mechanical Properties of Low Carbon UNS S41003 Stainless Steel - Lívia Ferreira Guedes; André Rocha Pimenta; Geronimo Perez; Rodrigo C. Paes Loureiro; Arthur C. Gonzaga; Sérgio S. M. Tavares (Materials Research)
UNS S41003 stainless steel is a lean stainless steel with 10.5-11% Cr, low carbon (<0.03%C), and small Ni addition. The composition is such that, depending on the processing route, the microstructure can be ferritic, martensitic, or ferritic-martensitic. Specimens acquired from the steelmaker were produced by hot rolling, with and without batch annealing. Two other sets of specimens were created by heat treating at 1000°C followed by water quenching. The microstructures of the four groups of specimens were characterized by scanning electron microscopy (SEM) with electron backscattered scanning diffraction (EBSD). The mechanical properties were measured by tensile tests, hardness, and impact toughness. This study demonstrates the optimal combination of mechanical resistance and toughness in hot rolling samples, which presented a fine grain size of martensite with fine carbides and 23.3% of elongated δ-ferrite. The hot rolled samples show a yield strength 6.2% higher than the quenched samples, and 152.1% higher than the annealed ones. The hot rolled steel presents a higher impact toughness, 31.7 J, 16.1% superior to the annealed material. The quenching heat treatments decreased the %δ ferrite and increased the grain size. The material annealed has a microstructure of equiaxial α-ferrite grains and intergranular chromium carbides.